2009
DOI: 10.1111/j.1365-2966.2008.14095.x
|View full text |Cite
|
Sign up to set email alerts
|

Satellite kinematics - II. The halo mass-luminosity relation of central galaxies in SDSS

Abstract: The kinematics of satellite galaxies reflect the masses of the extended dark matter haloes in which they orbit, and thus shed light on the mass–luminosity relation (MLR) of their corresponding central galaxies. In this paper, we select a large sample of centrals and satellites from the Sloan Digital Sky Survey and measure the kinematics (velocity dispersions) of the satellite galaxies as a function of the r‐band luminosity of the central galaxies. Using the analytical framework presented in More, van den Bosch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
214
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(248 citation statements)
references
References 40 publications
30
214
3
1
Order By: Relevance
“…The most common failure mode was the selection of satellites as MMGG scale because they had higher stellar masses than the true centrals, which happened in 12% of cases. The frequency of this occurrence depends on the way we populate halos with mock galaxies following the stellar-mass-halo-mass relation of Leauthaud et al (2012), but we note that scatter in this relation is consistent with that found in other analyses (Yang et al 2009;More et al 2009;Reddick et al 2012). The remaining centering failures were evenly split between cases where X-ray errors misplaced the search region and photometric redshift errors scattered centrals out of their groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most common failure mode was the selection of satellites as MMGG scale because they had higher stellar masses than the true centrals, which happened in 12% of cases. The frequency of this occurrence depends on the way we populate halos with mock galaxies following the stellar-mass-halo-mass relation of Leauthaud et al (2012), but we note that scatter in this relation is consistent with that found in other analyses (Yang et al 2009;More et al 2009;Reddick et al 2012). The remaining centering failures were evenly split between cases where X-ray errors misplaced the search region and photometric redshift errors scattered centrals out of their groups.…”
Section: Discussionsupporting
confidence: 90%
“…Groups and clusters form from mergers of halos where the most massive halo becomes the host halo with its central galaxy, and smaller halos become subhalos with satellite galaxies. Several analyses of data from group catalogs and field surveys have found that there is some intrinsic scatter in stellar mass and luminosity at fixed halo mass (Yang et al 2009;More et al 2009;Leauthaud et al 2012;Reddick et al 2012), which implies that halos can end up with satellites that are intrinsically more massive or luminous than the central galaxy. Additionally, there are uncertainties in measuring any observable quantity such as stellar mass that can cause a satellite to be misidentified as the most massive central galaxy, and structure projected along the line of sight can confuse the identification of member galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…However, an additional source of scatter is introduced when the stellar mass-halo mass relationship is applied. This scatter is on the order of 0.16-0.2 dex at z = 0, with the scatter presumably increasing with redshift (More et al 2009;Reddick et al 2012). A comparable analysis to that presented in this paper would be needed.…”
Section: Comparison To Tracking Galaxies With a Stellar Mass-halo Masmentioning
confidence: 98%
“…From a global perspective that includes all galaxies, tremendous progress has had been made in recent years in terms of understanding and modelling the connection between galaxy stellar mass and dark matter halo mass out to z = 1 and beyond (Mandelbaum et al 2006;More et al 2009;Behroozi, Conroy & Wechsler 2010;Moster et al 2010;Leauthaud et al 2011Leauthaud et al , 2012a. At the core of these models is the stellar-to-halo mass relation (SHMR) for central galaxies.…”
mentioning
confidence: 99%
“…In addition to the SHMR, these methods also constrain how satellite galaxies populate dark matter haloes as a function of galaxy mass. Finally, the SHMR may also be constrained as a function of other properties beyond stellar mass, such as galaxy colour or star formation activity (Mandelbaum et al 2006;More et al 2009;Hearin et al 2014;Tinker et al 2013).…”
mentioning
confidence: 99%